The Integration of Science and Religion in the Perspective of Islamic Educational Philosophy - Jundan Niswa Khoirunnisa; Muhammad Asrori (Al-Ulum: Jurnal Pendidikan Islam, 2026)
The research aims to analyze the concept of integrating science and religion within the philosophy of Islamic education and to examine its relevance and implications for the development of Islamic education in the digital and global era. The research employs a library research method with a descriptive-analytical approach through critical review of scholarly books, journal articles, and relevant empirical studies. The findings reveal that the integration of science and religion serves as an essential epistemological paradigm capable of constructing a holistic Islamic education oriented toward the formation of insan kamil. The study highlights that integrative education significantly strengthens students’ religious character, critical thinking skills, and academic competitiveness, while responding effectively to moral crises and dehumanization generated by modernity and digital disruption.